Leading cities : a global review of city leadership - Rapoport, Elizabeth; Acuto, Michele, 1984-; Grcheva, Leonora (UCL Press, 2019)
Leading Cities is a global review of the state of city leadership and urban governance today. Drawing on research into 202 cities in 100 countries, it offers an evidence-based and practical assessment of how cities are led, what challenges their leaders face, and the ways in which cities are increasingly connected to global affairs.